ASPEK REPRODUKSI IKAN LIDAH, Cynoglossus lingua H.B. 1822 DI PERAIRAN UJUNG PANGKAH, JAWA TIMUR [Reproductive aspect of long tonguesole, Cynoglossus lingua H.B 1822 in Ujung Pangkah Waters, East Java] - Sulistiono Sulistiono; Karlina D. Soenanthi (Masyarakat Iktiologi Indonesia (Indonesian Ichthyological Society), 2009)
This study aims to investigate gonad maturity of long tonguesole (Cynoglossus lingua). Samples were collected from August 2005 to Januari 2006 from fish caught by fishermen using gill net and trap net in Ujung Pangkah waters. Analysis was done to estimate gonad maturity, gonado-somatic index, fecundity, and oocyte diameter. Long tonguesole was 202 individual consisted of 94 male and 108 female fish varied 65-325 mm in total body length. Sex ratio was around 1:1.4. First maturity gonad of male and female fish was 94-122 mm. According to gonad maturity stage and gonadosomatic index, fish was estimated to spawn from August to January with a peak one during December. Fecundity was 360-35926 eggs and oocyte diameter was 0.08-0.63 mm. Based on oocyte distribution, the fish was estimated a partial spawner.